The Effect of Using Netsupport School Software on Environmental Pollution Subject Matter on Student Learning Outcomes - zuhair abdullah (Indonesian Journal of Science and Education (IJOSE), 2021)
This study aims to determine the effect of using NetSupport School software on environmental pollution subject matter on student learning outcomes. This is a quasi-experimental research. The research design used is a posttest only control group design. The research sample consisted of three groups taken randomly. The first group is the control group which does not use learning multimedia, the second group is experiment group 1 which uses an LCD projector, and the third group is experiment group 2 using NetSupport School software. The data collection instruments are in the form of posttest questions and affective questionnaire sheets. The data analysis technique was carried out using the One-Way ANOVA test. The results showed that: 1). hypothesis testing of cognitive learning outcomes showed that there was a significant effect on all groups. Of the three groups, experiment group 2 had the highest mean value. 2). the hypothesis test of affective learning outcomes showed that there was a significant effect on all groups. Of the three groups, experiment group 2 had the highest mean value. Based on these results, it is concluded that the NetSupport School software application has a significant effect on students’ cognitive and affective learning outcomes.